Design of a Software Requirements Specification for a Parental Partnership Assistance Management System in Elementary School in Malang Regency - Christian Difae Klemens; Meme Susilowati (Yayasan Kita Menulis, 2026)
This research is motivated by the need for a more efficient and transparent aid management system in primary education institutions, particularly at SDK Yos Sudarso Kepanjen, where the processes of application, verification, and reporting are still conducted manually. Such conditions lead to various issues, including delayed distribution, data duplication, and difficulties in monitoring assistance. To address these problems, a Software Requirements Specification (SRS) document was designed as a reference for developing a web- and mobile-based Parent Partnership Aid Management Information System. This study employed a system engineering approach consisting of three main phases: analysis, design, and implementation. These phases include problem identification, system workflow redesign, and the development of an initial user interface prototype using HTML and CSS (Bootstrap framework). The results indicate that the SRS document successfully defines the system’s functional and non-functional requirements, including user authentication, aid application, digital verification, automated reporting, and a GPS-based needs mapping feature. It is expected that this SRS document can serve as a guideline for developing collaborative, efficient, and accountable educational information systems in the future.